Comparison of External Fixation and Supplementary Kirschner-Wires Fixation with Volar Locking Plate for the Treatment of Intra- Articular Distal End Radius Fractures - Dwivedi, Rajeev; Khatri, Mandir; KC, Arjun (Journal of Lumbini Medical College, 2020)
Introduction: There are controversies regarding the benefit of open reduction and internal fixation with volar locking plates over closed reduction and external fixation along with supplementary Kirschner wires fixation for intra-articular distal end radius fracture.Therefore, this study aimed to compare the outcomes between external fixation along with supplementary Kirschner wires with volar locking plate in the treatment of intra-articular distal end radius fractures. Methods: This prospective, observational and analytical study was conducted over one and a half years. Forty-seven adults with displaced intra-articular distal end radius fracture were included in the study. Twenty-one cases were treated with closed reduction and external fixation along with supplementary Kirschner wires, whereas 26 patients were treated with open reduction and volar locking plate fixation. Results: At the end of three months, as per the Green and O’Brien scoring, the mean functional outcome score in the volar plate group was significantly better 80.77(±11.46) than the external fixation group 70.24(±10.66) (p=0.002). However, at the end of six months, the mean score in the volar plate group 86.15(±7.39) was not significantly different from the external fixation group 81.43(±9.63) (p= 0.63). Fracture reduction was achieved and maintained better in the volar locking plate group. Conclusion: Functional outcome of closed reduction and external fixation along with supplementary Kirschner wires is comparable with open reduction and internal fixation by volar locking plate in treatment of displaced intra-articular distal radius fractures. Radiological correction is achieved and maintained better with volar locking plates.